2013
DOI: 10.1074/jbc.m112.444760
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Amino Acids within the Nucleoprotein of Tacaribe Virus Important for Anti-interferon Activity

Abstract: Background: With the exception of Tacaribe virus, all arenavirus nucleoproteins are thought to inhibit type I interferon production. Results: Variation in nucleoprotein residues 389 -392 of Tacaribe virus was characterized as a critical region regulating interferon inhibition. Conclusion: Some Tacaribe virus variants contain the important nucleoprotein residues necessary for interferon antagonism. Significance: Anti-interferon activity of nucleoproteins appears to be a conserved feature of all arenaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
4
23
1
Order By: Relevance
“…As this manuscript was in review, an independent study has been published by Harmon et al (31) to describe the role of TCRV NP in suppressing IFN-β production, which reinforces our finding.…”
supporting
confidence: 89%
“…As this manuscript was in review, an independent study has been published by Harmon et al (31) to describe the role of TCRV NP in suppressing IFN-β production, which reinforces our finding.…”
supporting
confidence: 89%
“…The RNase function of NPs is required for inhibition of PACT-RIG-I-induced IFN-␤ promoter activation. We and other researchers have shown that NP RNase activity was required for its inhibition of type I IFN production (33)(34)(35)(36)(37)(38)(39)(40). To determine whether the RNase activity of NP was also necessary to inhibit PACT-RIG-I-induced IFN-␤ promoter activities, plasmids carrying either WT LASV NP, LASV NP with a known RNase-defective mutation (D389A) (34,38), the C-terminal RNase-containing LASV NP The experiments that generated data for each of the panels shown were repeated three times.…”
Section: Arenaviral Nucleoproteins Block Pact-augmented Rig-i-inducedmentioning
confidence: 93%
“…Specifically, the EBOV VP35, IAV NS1, HSV-1 Us11, MERS-CoV 4a and nucleocapsid (N), as well as MHV N proteins have been shown to directly abolish the interaction between RIG-I and PACT and, hence, block the ability of PACT to activate RIG-I (24,(26)(27)(28)(29)32). We and other researchers have shown previously that arenaviral nucleoproteins (NPs) can efficiently suppress type I IFN production by degrading immunostimulatory RNAs via their intrinsic 3=-to-5= exoribonuclease activity (33)(34)(35)(36)(37)(38)(39)(40). In the present study, we show that LASV NP effectively blocked the PACT-induced augmentation of RIG-I function and therefore suppressed type I IFN production.…”
mentioning
confidence: 99%
“…It is therefore possible to envision the possibility that such processing removes from the viral dsRNA any PAMP hallmark that would be otherwise recognized by RLRs. The fact that critical residues for dsRNA exoribonuclease-mediated IFN inhibition are highly conserved among the NPs of all arenaviruses strongly suggests that this form of the Mask strategy is widely shared within the family (Harmon et al, 2013;Jiang et al, 2013;Qi et al, 2010).…”
Section: Maskmentioning
confidence: 99%